Scale Up BUMDes Through Digitalization and Network Development at BUMDes in Lumintu, Mojorembun, Blora District - Nur Fitri, Alifa; Rahmi, Amelia; Hilmi, Mustofa; Diyana, Dinunah; Prasetyo, Kurniawan (Prosperity: Journal of Society and Empowerment, 2025)
This study aims to assess the impact of the Asset-Based Community-Driven Development (ABCD) approach on the development of Village-Owned Enterprises/Badan Usaha Milik Desa (BUMDes) in Lumintu Village, Mojorembun Village, Blora District. The scope of the research includes aspects of organisational management, product digitalization, network development, and public relations. The method used was descriptive qualitative. Data collection techniques used interviews, observation, and documentation. The assistance was conducted through product digitalization training, company profile video creation, and social media optimisation, which proved to expand the market reach and improve the operational effectiveness of BUMDes. The results show that digital transformation and strengthening the organisational structure can improve business competitiveness and strengthen strategic networks with the government and neighbouring companies. These findings provide important empirical evidence on the effectiveness of an asset-based approach in empowering rural communities economically. This study also confirms the urgency of digitalization for microenterprise development in rural areas. Recommendations for future research include a quantitative impact analysis of digitization with a broader scope and an exploration of more effective networking strategies. These will support the development of a sustainable rural empowerment model.